IFPRI-Sudan: Generating evidence-based solutions for strengthening humanitarian response and economic resilience - Siddig, Khalid; Abay, Kibrom A.; Kirui, Oliver K.; Abushama, Hala; Mohamed, Shima; Rakhy, Tarig (International Food Policy Research Institute, 2025)
Sudan is experiencing one of the most severe humanitarian and economic crises in its modern history due to the ongoing conflict between the Sudanese Armed Forces (SAF) and the Rapid Support Forces (RSF). Sudan is now suffering the largest humanitarian crisis in the world. The war has devastated livelihoods, displaced millions, and significantly weakened the country’s agrifood systems and broader economic structures. In response, the International Food Policy Research Institute (IFPRI), along with its partners, has intensified its research and policy engagement in Sudan through the Sudan Strategy Support Program (SSSP), which was launched in 2022.